2013
DOI: 10.1016/j.socscimed.2012.11.039
|View full text |Cite
|
Sign up to set email alerts
|

How robust is the evidence of an emerging or increasing female excess in physical morbidity between childhood and adolescence? Results of a systematic literature review and meta-analyses

Abstract: For asthma and psychological morbidity, it is well established that higher prevalence among males in childhood is replaced by higher prevalence among females by adolescence. This review investigates whether there is evidence for a similar emerging female ‘excess’ in relation to a broad range of physical morbidity measures. Establishing whether this pattern is generalised or health outcome-specific will further understandings of the aetiology of gender differences in health. Databases (Medline; Embase; CINAHL; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 83 publications
2
21
0
1
Order By: Relevance
“…gender differences were found in that girls reported higher extrinsic effort and higher overcommitment than boys. In line with previous research [1,2,23,24], girls reported worse overall and somatic health than boys. For self-rated health the most important gender difference was that a substantially greater share of boys than girls reported 'Very good' health.…”
Section: Discussionsupporting
confidence: 92%
“…gender differences were found in that girls reported higher extrinsic effort and higher overcommitment than boys. In line with previous research [1,2,23,24], girls reported worse overall and somatic health than boys. For self-rated health the most important gender difference was that a substantially greater share of boys than girls reported 'Very good' health.…”
Section: Discussionsupporting
confidence: 92%
“…In order to awaken interest in these kinds of programs and make them effective, they must be adapted to the demands of contemporary society. Therefore, the use of new technologies could be applied, such as the creation of educational blogs in which students participate actively or the use of mobile applications for adequate consumption of food and for the practice of physical activity [37,38]. It is also interesting for participants to experience all this in workshops designed by specialists in each of the affected areas, so that prevention is reinforced with active, cooperative, and collaborative learning.…”
Section: Discussionmentioning
confidence: 99%
“…Although social disadvantage is not frequently cited as a social factor in LBP disability, social and economic disadvantage is certainly associated with poorer outcomes in other health domains [57,58]. Longitudinal studies of LBP prognosis typically include demographic assessments of age, gender, income, education and race/ethnicity, and these variables might be considered as a general metric of social standing.…”
Section: Social Disadvantagementioning
confidence: 99%